Epigenetics and epilepsy prevention: The therapeutic potential of adenosine and metabolic therapies. (1st May 2020) - Boison, Detlev; Rho, Jong M.
Abstract: Prevention of epilepsy and its progression remains the most urgent need for epilepsy research and therapy development. Novel conceptual advances are required to meaningfully address this fundamental challenge. Maladaptive epigenetic changes, which include methylation of DNA and acetylation of histones – among other mechanisms, are now well recognized to play a functional role in the development of epilepsy and its progression. The methylation hypothesis of epileptogenesis suggests that changes in DNA methylation are implicated in the progression of the disease. In this context, global DNA hypermethylation is particularly associated with chronic epilepsy. Likewise, acetylation changes of histones have been linked to epilepsy development. Clinical as well as experimental evidence demonstrate that epilepsy and its progression can be prevented by metabolic and biochemical manipulations that target previously unrecognized epigenetic functions contributing to epilepsy development and maintenance of the epileptic state. This review will discuss epigenetic mechanisms implicated in epilepsy development as well as metabolic and biochemical interactions thought to drive epileptogenesis. Therefore, metabolic and biochemical mechanisms are identified as novel targets for epilepsy prevention. We will specifically discuss adenosine biochemistry as a novel therapeutic strategy to reconstruct the DNA methylome as antiepileptogenic strategy as well as metabolic mediators, such as beta-hydroxybutyrate, which affect histone acetylation. Finally, metabolic dietary interventions (such as the ketogenic diet) which have the unique potential to prevent epileptogenesis through recently identified epigenetic mechanisms will be reviewed. This article is part of the special issue entitled 'New Epilepsy Therapies for the 21st Century – From Antiseizure Drugs to Prevention, Modification and Cure of Epilepsy'. Highlights: Epigenetic changes contribute to epilepsy development. Hypermethylation of DNA is associated with the epileptic state. Adenosine therapy restores normal DNA methylation levels and prevents epileptogenesis. Histone acetylation changes are associated with epilepsy. Metabolic therapies, such as ketogenic diets, block histone deacetylases and raise adenosine.